The studio as study: reflections on the establishment of doctoral programmes in fine art - Reed-Tsocha, Katerina (PORTO ARTE: Revista de Artes Visuais, 2013)
This article joins the debate on the exact nature of the doctorate in fine art, a well-established qualification in some countries but more recent venture across art schools in the United Kingdom and the United States. Taking as a starting point the experience of establishing and developing the doctoral programme of the Ruskin School of Drawing and Fine Art at the University of Oxford, I address questions of the overall rationale for the introduction of this research degree, the integration of fine art graduate programmes within the research environment of larger academic institutions, as well as the orientation and components of doctoral projects. A further question that is raised is the danger of loss of autonomy and the excessive academicization of artistic practice and its potential deterioration into illustration of theoretical ideas.